Differentiation of Self as a Predicting Factor of Church Activists’ Well-Being in Indonesia - Kenneth Girvan; Yonathan Aditya (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2025)
Intense religious ministry demands often lead to stress and burnout, which in turn affect personal well-being. This study aims to examine whether differentiation of self can predict the well-being of church activists in Indonesia. The hypothesis proposed is maintaining identity and relational sensitivity would positively contribute to well-being, whereas emotional distancing would contribute negatively. This research employed a quantitative, non-experimental with total of 109 church activists in the Greater Jakarta area participated through an online survey using purposive sampling. Data were analyzed using Spearman’s correlation and multiple regression via the JASP program. The results indicated that differentiation of self significantly predicted well-being. Specifically, maintaining identity positively contributed to well-being (β = .37, p .01), while emotional distancing contributed negatively (β = −.29, p = .01), and relational sensitivity was not a significant predictor (β = −.10, p = .29). These findings suggest that the ability to maintain a stable sense of identity under pressure and to sustain a balanced emotional distance plays an important role in enhancing the well-being of church activists.